The Association of Hygiene Sanitation Storing and the Presence of Escherichia coli Bacteria at Sambel Tumpang - Pujianto, Tutut (Journal of Global Research in Public Health, 2018)
Pecel tumpang is one of the typical traditional culinary of Kabupaten Kediri which has been known worldwide. The leftover sambel tumpang (kind of sauce) which is served in one day, usually be stored and be sold for the next day. The improper storing of it will result in the contamination of microorganisms in sambel tumpang. The occurrence of contamination in storing stage is caused by the cook/ chef hygiene, the storing sanitation treatment, the sanitation of the equipments, and the storing sanitation environment. This study aimed to analyze the association of Hygiene Sanitation Storing and the Presence of Escherichia coli Bacteria. This study used observational design with cross-sectional approach. It was conducted on 15 nasi pecel tumpang vendors in kampong Inggris. The analysis of the association between storing sanitation and the presence of E.coli used the contingency coefficient test (Î±=5%). The results of the association analysis between storing sanitation and the presence of E. coli were as follows: there was no association between cook/chef hygiene with the presence of E. coli, there was no association between storing treatment and the presence of E. coli, there was no association between sanitation of the equipment and the presence of E. coli , there was a significant association between storing sanitation environment and the presence of E. coli. The condition of storing sanitation environment of sambel tumpang in Kampung Inggris was very supportive to the growth and development of the microorganism, both bacteria and mold. The environmental conditions included moist air, non waterproof floor, the source of contaminants such as waste, and the presence of insects / flies. In order to prevent the contamination of E. coli, the vendors must pay attention to the state of the environment. The storing environment of sambel tumpang should always be freed from trash and insects / flies, and never forget to secure and close the sambal tumpang